Global Financial Stability Report, April 2017 : Getting the Policy Mix Right. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
Financial stability has continued to improve since the October 2016 Global Financial Stability Report (GFSR). Economic activity has gained momentum, as outlined in the April 2017 World Economic Outlook (WEO), amid broadly accommodative monetary and financial conditions, spurring hopes for reflation. Chapter 2 analyzes the potential long-term impact of a scenario of sustained low growth and low real and nominal rates for the business models of financial institutions and the products offered by the financial sector. Chapter 3 examines whether countries still retain influence over their domestic financial conditions in a globally integrated financial system. The chapter develops financial conditions indices that make it possible to compare a large set of advanced and emerging market economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet